Analisis Dan Pengujian Test Case Rancang Bangun Aplikasi Helpdesk Ticketing Berbasis Web Dengan Metode Scrum - Dhimas Suryo Laksono; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
Managing customer complaints and service requests often encounters obstacles in manual systems, such as delayed response times, lost ticket data, and the absence of status tracking. This research aims to design and develop a web-based helpdesk ticketing application to automate ticket management processes more efficiently.The development method adopts the waterfall approach, encompassing requirements analysis, system design (including UML diagrams such as use case, class, sequence, and activity), implementation using the PHP framework, MySQL database, and Bootstrap for responsive interfaces. The application supports key features like ticket creation by users, ticket assignment to agents, real-time status tracking, email notifications, and analytical reports.Testing results indicate the application operates optimally with a 95% success rate on functional and non-functional tests, and an average response time under 2 seconds. The application successfully enhances helpdesk management efficiency by up to 40% based on simulated data. In conclusion, this system is feasible for implementation in organizations with high ticket volumes, with suggestions for further development such as AI integration for ticket prioritization.